ACALCULIA IN PATIENT WITH BROCA APHASIA AND MILD COGNITIVE IMPAIRMENT - A CASE STUDY - Červinková, Helena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Acalculia is an acquired disorder of calculating which occures isolated or with association with aphasia and mild cognitive impairment. We described a case study of 37-year-old Ms. R. after hemorrhage and ischemia with Broca aphasia and acalculia in the article. Ms. R. was assessed by own diagnostic test for acalculia, by test for aphasia and cognitive functions. The aim of the study was to investigate the link between Ms R.´s acalculia, Broca aphasia nad mild cognitive impairment. Assessment revealed Broca aphasia, verbal apraxia, alexia, agraphia, poor attention, weak working memory and poor later recall of remembered words. Assessment of acalculia showed transcoding impairments, disorders of aritmetic fact retrieval and disorders of calculation procedures. Poor working memory and alexia influenced transcoding of numbers. Alexia is also manifested in comprehension of word problems. Counting backward and counting dots were complicated by poor concentration of attention and weak working memory. Symptoms of aphasia, acalculia and mild cognitive impairment affected each other.